Freud did not invent Nietzsche - Śliwierski, Andrzej (Studia Psychologica: Theoria et praxis, 2006)
This article focuses on the origins of Sigmund Freud.s theory, which is sometimes thought to be a mixture of different human conceptions. Moreover, Freud is often being accused of having stolen the ideas of Meynert, Charcot, Breuer, and Janet. However, the aim of this article is to prove that the main source of Freud.s theory was the philosophy of Friedrich Nietzsche. Both Nietzsche.s and Freud.s works share striking similarities, such as examples employed to illustrate their theories. Naturally, it is impossible to accuse Freud of plagiarism on the grounds of the aforementioned similarities alone. Furthermore, the famous psychologist himself denied having even read Nietzsche.s books and claimed that it was precisely this lack of knowledge of related literature that contributed to his innovatory way of thinking. What is more, Freud tried to demonstrate that he was the first .conqueror of unconsciousness. and basically created an image of himself as a great scientist who revolutionized both psychology and psychiatry. This article, however, looks at the biography of Sigmund Freud and argues that his denial that he ever read Nietzsche.s works was nothing but a lie. Afterward, an attempt is made to identify which of Freud.s conceptions are similar to Nietzsche.s ideas.